Highly Efficient Silylative Kinetic Resolution of Racemic trans‐2‐Alkyl‐1‐indanols Catalyzed by Chiral Guanidine. Issue 41 (2nd November 2021) - Suzuki, Takeshi; Iwakura, Manaya; Nakata, Kenya
Abstract: Chiral guanidine catalyzed silylative kinetic resolution of racemic trans ‐2‐alkyl‐1‐indanols using Ph3 SiCl was achieved with high s ‐values. A variety of substrates bearing alkyl groups at the C‐2 position and substituents on the aromatic rings of the indanol moiety were applicable in the reaction achieving good to high selectivity, irrespective of the type of substituent present. In addition to exhibiting high selectivity, the guanidine catalyst was found to be highly active and the reactions could be performed using a catalyst loading of only 0.5 mol %. It was revealed that the relative stereochemistry of the stereogenic centers of the substrates was important and that the reaction using cis ‐substrates did not proceed at all, whereas the reaction can be selectively carried out using trans ‐substrates. Abstract : Key Topic: Kinetic ResolutionSilylative kinetic resolution of racemic trans ‐2‐alkyl‐1‐indanols using Ph3 SiCl was achived with high s ‐values, catalyzed by chiral guanidine. It was revealed that only 0.5 mol % of the catalyst was sufficient for the reaction to attain high reactivity and selectivity.